Analysis of corrugation evolution characteristics based on scale-down tests – contact stick-slip perspective - Zhiqiang Wang; Pengfei Liu (Railway Sciences, 2025)
Purpose – Rail corrugation is still one of the unsolved challenges in the railway industry, and the abnormal vibration and high-frequency noise caused by it constitute serious adverse effects on the operating environment. How to control corrugation has been an important research theme, and understanding corrugation evolution features is the necessary prerequisite. This study aims to investigate the specific evolution characteristics of corrugation from the contact stick-slip perspective. Design/methodology/approach – The formation and development processes of corrugation are analyzed by using a self-designed scale-down test device. Specifically, the contact stick-slip characteristics under different creepage conditions are analyzed and the formation mechanism of corrugation is summarized. On the basis of corrugation formation, the trend of corrugation development is further emphasized to completely describe the whole process of corrugation evolution. Findings – The results show that, under the determined vertical load condition, the contact interface appears the creep force-creepage negative slope phenomenon in the transverse direction. The cause of short-pitch corrugation on the rail wheel surface under the smaller angles of attack may be related to the inherent vibration frequency of the test device, and the cause of corrugation on the rail wheel surface under the larger angles of attack is mainly related to the stick-slip vibration induced by contact creep saturation. Originality/value – This research explores the evolution characteristics of corrugation by adopting a self-designed scale-down test device, and elucidates the mechanism of corrugation in detail.